The GDP-Mannose Dehydrogenase of Pseudomonas aeruginosa: An Old and New Target to Fight against Antibiotics Resistance of Mucoid Strains - Christian Hulen (MDPI AG, 2023)
Alginates play an important role in the resistance of mucoid strains of Pseudomonas aeruginosa to antibiotics, as well as their persistence by escaping the immune defense system. GDP-mannose dehydrogenase (GMD) is the key enzyme in alginate biosynthesis by catalyzing the irreversible double oxidation of GDP-mannose to GDP-mannuronate. GDP-mannose dehydrogenase purified from mucoid strains exhibits strong negative cooperativity for its substrate, the GDP-mannose, with a KM of 13 µM for the site of strong affinity and 3 mM for this weak of a binding. The presence of a nucleotide strongly associated with the enzyme was detected, confirming the fact that the substrate oxidation reaction takes place in two distinct steps, with the substrate blocked on the enzyme in a half-oxidation state in the form of a hemiacetal. As the GMD polypeptide has only one site for substrate binding, our results tend to confirm the fact that the enzyme functions in a dimer form. The GDP-mannose dehydrogenase inhibition strategy that we developed a few years ago, based on the synthesis of substrate analogs, has shown its effectiveness. The addition of an alkynyl radical on carbon 6 of the mannose grafted to an amino-sulfonyl-guanosine allows, at a concentration of 0.5 mM, to inhibit GMD by 90%. As we had previously shown the effectiveness of these analogs on the sensitivity of mucoid strains of Pseudomonas aeruginosa to aminoglycosides, this revives the interest in the synthesis of new inhibitors of GDP-mannose dehydrogenase.